On infinite class of strongly collision resistant hash functions” edon-f” with variable length of output - Gligoroski, Danilo; Markovski, Smile; Bakeva, Verica (My University, 2003)
Two infinite classes of strongly collision free hash functions “Edon-C” and “Edon-R” are defined in [GMB 2003]. Here we propose one more hash function of similar ‘Edon’ type called “Edon-F”. This hash function is based on the theory of quasigroups and the cryptographic properties of quasigroup string processing, i.e. by similar idea as the others ‘Edon’ type of hush functions are designed. The “Edon-F” hash function is designed in such a way to be much faster than “EdonC” and “Edon-R”, i.e. it is with linear complexity. The price for that is paid on the security level, in the sense that the length of the output message (the message digest) should be enough large
Keywords: quasigroup, one-way function, hash function